Persisting Microbiota and Neuronal Imbalance Following T. gondii Infection Reliant on the Infection Route - French, Timothy; Steffen, Johannes; Glas, Albert; Osbelt, Lisa; Strowig, Till; Schott, Björn H.; Schüler, Thomas; Dunay, Ildiko Rita (Frontiers in Immunology, 2022)
Toxoplasma gondii is a highly successful parasite capable of infecting all warm-blooded animals. The natural way of infection in intermediate hosts is the oral ingestion of parasite-contaminated water or food. In murine experimental models, oral infection (p.o.) of mice with T. gondii is applied to investigate mucosal and peripheral immune cell dynamics, whereas intraperitoneal infection (i.p.) is frequently used to study peripheral inflammation as well as immune cell – neuronal interaction in the central nervous system (CNS). However, the two infection routes have not yet been systematically compared along the course of infection. Here, C57BL/6 mice were infected p.o. or i.p. with a low dose of T. gondii cysts, and the acute and chronic stages of infection were compared. A more severe course of infection was detected following i.p. challenge, characterized by an increased weight loss and marked expression of pro-inflammatory cytokines particularly in the CNS during the chronic stage. The elevated proinflammatory cytokine expression in the ileum was more prominent after p.o. challenge that continued following the acute phase in both i.p. or p.o. infected mice. This resulted in sustained microbial dysbiosis, especially after p.o. challenge, highlighted by increased abundance of pathobionts from the phyla proteobacteria and a reduction of beneficial commensal species. Further, we revealed that in the CNS of i.p. infected mice CD4 and CD8 T cells displayed higher IFNγ production in the chronic stage. This corresponded with an increased expression of C1q and CD68 in the CNS and reduced expression of genes involved in neuronal signal transmission. Neuroinflammation-associated synaptic alterations, especially PSD 95, VGLUT and EAAT2 expression were more pronounced in the cortex upon i.p. infection highlighting the profound interplay between peripheral inflammation and CNS homeostasis.